DOES YOUR EVENT LOG FIT THE HIGH-LEVEL PROCESS MODEL? - A. K. Begicheva; I. A. Lomazova (Моделирование и анализ информационных систем, 2015)
Process mining is a relatively new field of computer science, which deals with process discovery and analysis based on event logs. In this paper we consider the problem of models and event logs conformance checking. Conformance checking is intensively studied in the frame of process mining research, but only models and event logs of the same granularity were considered in the literature. Here we present and justify the method of checking conformance between a high-level model (e.g. built by an expert) and a low-level log (generated by a system).The article is published in the author’s wording.